THE RELATIONSHIP BETWEEN FEAR OF MISSING OUT (FOMO) AND SOCIAL MEDIA ENGAGEMENT AMONG STUDENTS AT SEMARANG STATE UNIVERSITY - Hanantoro, Zain Azmi; Munawaroh , Eem (LP2M IAI Al-Khairat Pamekasan, 2026)
Rapid technological advances coupled with high mobile connectivity have driven an increase in social media usage, particularly among students. This is because students are in the emerging adulthood phase, a transitional phase from late adolescence to early adulthood, during which social media is often used to support developmental tasks. However, intensive social media use also poses risks to mental health, one of which is the emergence of the phenomenon known as fear of missing out (FoMO). FoMO drives the urge to stay constantly connected to social media, potentially leading to excessive digital consumption patterns. This study aims to analyze the relationship between fear of missing out (FoMO) and social media engagement among students at Semarang State University as a basis for formulating strategies to optimize social media use and prevent its negative impacts. This study used a quantitative approach with a correlational research design, and the data analysis technique used was simple linear regression. The population in this study consisted of 375 students selected using proportional stratified random sampling. The instruments used included the Fear of Missing Out Scale: FoMOs and the Social Media Engagement Scale for Adolescents (SMES-A). Data analysis revealed a positive correlation between fear of missing out and social media engagement, with values of R = 0.952, R² = 0.907, and B = 0.721. These results indicate that an increase in fear of missing out influences students' social media engagement. This finding underscores the importance of interventions that promote healthy and proportional use of social media.